TINJAUAN KRITIS PENGARUH MEDIA SOSIAL: SEBAB BERGESERNYA KARAKTER ORANG - Saipul Saipul (Tabayyun: Journal of Journalism, 2021)
It is time to criticize the use of social media in the form of Instagram, Telegram, Facebook because its users are widespread in society. Social users spread rapidly to the younger generation or school-age children. So this is where there is a problem, namely content that violates religious, cultural, and traditional norms that live in society. The tendency of destructive social media content often destroys religious, cultured, and local wisdom people in people's lives. The ideal characters expected in society include piety, honesty, always learning. By implication the W5H1 method as a critical attitude to social media content, so that a wise attitude in using social media is used as a tool for analysis by social media users. Keywords: Social Media, Content, Character